Impact of Nutrition Training on Long-Term Adoption of High-Zinc Rice: A Randomized Control Trial Study among Female Farmers in Bangladesh - CGIAR Research Program on Rice (2021)
A key constraint on the adoption of biofortified crops is the limited understanding of the need for micronutrients among farmers. In Bangladesh, high-zinc rice varieties have been developed and released to address the problem of zinc deficiency, particularly among children and pregnant women. The study use randomized control experiment to examine the impact of nutrition training on the adoption of a High-Zinc Rice BRRI Dhan72. Results indicate that nutrition training has a long-term but diminishing impact on high-zinc rice adoption.